Synodality as a framework for Christian-Muslim Dialogue in Asia - Pablito A. Baybado (Muslim Politics Review, 2025)
In Asia, where Catholicism constitutes a minority religion except in the Philippines and Timor-Leste, Catholic Christians face the complex task of integrating into a culturally diverse and politically unstable landscape while preserving and asserting their distinct identity. This challenge mirrors the broader experience of minority religious communities coexisting with a dominant religion, particularly in contexts where the majority faith aligns with state or national identity. The interplay between the state and the majority religion often complicates integration efforts or deepens the isolation of the minority faith, while simultaneously fostering distrust among minority adherents toward both the majority and the state apparatus. Consequently, this majority-minority dynamic undermines initiatives aimed at dialogue and collaboration. The relationship between minority and majority religions is thus shaped by state policies and national interests, suggesting that the religious dimension of these intricate interactions is highly vulnerable to political discourses and movements, as explained in the theories of Antonio Gramsci. This article investigates these tensions through a comparative analysis of Christian-Muslim relations in the Philippines (majority Christian, minority Muslim) and Indonesia (majority Muslim, minority Christian). The analysis seeks to elucidate the critical factors generating friction within minority-majority dynamics and to assess the influence of state policies and national priorities on these interactions. The article explores potential avenues for mitigating these challenges through the implementation of the concept of synodality. Synodality is a process currently employed by the Catholic Church for its renewal and adaptation to contemporary demands. Synodality not only serves as a mechanism for Christian revitalization but also offers a robust theoretical framework for analyzing these issues, aiming to foster an effective interreligious dialogue that promotes mutual respect and cooperation across religious communities in Indonesia and the Philippines. By employing synodality as a relational paradigm, this study argues for the dismantling of the majority-minority binary, progressively eliminating barriers to authentic dialogue and collaborative engagement.